Transição de carreira de atletas do futsal paranaense - Passos, Patricia Carolina Borsato (2014)
This study aimed at investigating the process of athletic career transition for futsal players in Paraná taking part in the National League of 2013. The methodological strategy applied was the Bronfenbrenner's Bioecological model (1995, 1996, 2011) composed of four components: person, process, context and time (PPCT) the theoretical support was through the Developmental Model of Transitions faced by athletes (WYLLEMAN; LAVALLEE, 2003). The subjects were 75 male athletes of five teams from Paraná in the National League. The instruments applied were: identification form, journal of semi-structured research and interview, Sport Motivation Scale, Coping Strategies Questionnaire. The data collection was carried out collectively under previous scheduling by the teams technical commission, the interview was individually conducted recorded through a mini recorder and subsequently transcribed. The quantitative data analysis used: the Kolmogorov Smirnov, Friedman tests and multiple comparison of means distributions for all orders, the Spearman U test by Mann Whitney, applying p<0.05. The interviews used category type content analysis, the transcription was conducted in full. The results pointed that the athletes: are intrinsically motivated, present high levels of satisfaction and use coping strategies, maximum performance under pressure, confidence and motivation. The athletes presented higher efforts regarding both athletic and psychological domains, the least favored domains are the psychosocial and the academic/professional. The futsal athletes received Family support during their transition process as well as established good interpersonal relationships in the context prioritizing the athletic domain rather than the psychosocial and academic domains. All changes occurred with good adaptation skills and great efforts towards sport.